Kontribusi Trait Kepribadian terhadap Psychological Well-Being pada Komunitas Lansia “X” di Kota Bandung - Juliyanti Juliyanti (Humanitas (Jurnal Psikologi), 2018)
The purpose of this study was to build mental awareness of the psychological well-being of the elderly in the elderly community "X" in the city of Bandung. The method used is a functional technique with convenience sampling technique. The measuring instrument of psychological well-being has a validity range from 0.332 to 0.851, trait personality from 0.319 to 0.814 and reliability testing with the results of psychological health measurements having a reliability range of 0.444 to 0.839, personality trait 0.461 to 0.564. This questionnaire was given to 81 elderly people. Adjusting the analysis conducted in this study can be concluded that personality trait has a significant psychological well-being of 39.5%. Trait personality together has a significant psychological well-being of 21.2% in the elderly community "X" in the city of Bandung. Significant personality traits are neuroticism and extraversion. Keywords: elderly, psychological well-being, personality trait